2021
DOI: 10.1080/17483107.2021.1967469
|View full text |Cite
|
Sign up to set email alerts
|

Aided language modelling, responsive communication and eye-gaze technology as communication intervention for adults with Rett syndrome: three experimental single case studies

Abstract: Purpose: To examine the effect of a communication intervention package on expressive communication and visual attention in individuals with Rett syndrome. Materials and methods: A modified withdrawal (A-B1-A1-B2-A2) single case experimental design with a direct inter-subject replication across three participants was applied. Three women with Rett syndrome participated. The study took place over a six-week period and comprised 32 sessions with each participant. All sessions were video recorded. During the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…An exploratory case format focusing on the communication partner’s use of responsive strategies in dyadic interactions with three adults diagnosed with Rett syndrome was applied. The data were collected in an intervention study presented elsewhere ( Wandin et al, 2021 ). During eight of 14 of the interactions, the communication partner used aided AAC modeling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An exploratory case format focusing on the communication partner’s use of responsive strategies in dyadic interactions with three adults diagnosed with Rett syndrome was applied. The data were collected in an intervention study presented elsewhere ( Wandin et al, 2021 ). During eight of 14 of the interactions, the communication partner used aided AAC modeling.…”
Section: Methodsmentioning
confidence: 99%
“…The vocabulary consisted of core words, comments, feelings, actions, descriptions, and activity-specific pages. The interactions took place under two conditions that were the two first phases in an intervention study presented elsewhere ( Wandin et al, 2021 ):…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has suggested various methods to improve communication for individuals with Rett syndrome. For instance, Wandin et al (2021) found that aided language modeling and interactive partner techniques increased vocabulary use. Koppenhaver et al (2001) found that hand splints, assistive tools, and parental instruction improved decoding of communication attempts.…”
Section: Rett Syndrome and Aacmentioning
confidence: 99%
“…Previous research has shown that individuals diagnosed with Rett syndrome employ a diverse range of modalities to fulfill their communication objectives, such as vocalizations, facial expressions, body movements, and eye contact (Vessoyan et al, 2018; Bhattacharya & Pradana, 2022). Within these communication methods, intentional use of eye gaze has been reported as the most frequently observed mode of communication (Wandin et al, 2021). Therefore, employing AAC strategies that extend beyond oral speech, particularly through AAC systems featuring innovative eye gaze technology, is a viable approach to unlocking the communicative capabilities of individuals with Rett syndrome (Wandin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that the device provided substantial benefits to mediate communication within families. Further, Wandin, Lindberg, and Sonnander (2021) examined the efficacy of communication intervention in individuals with Rett syndrome and suggested that aided language modeling, responsive partner strategies, and the use of gaze-controlled devices could effectively increase expressive communication in individuals with Rett syndrome. While these studies have illuminated the complex, rich, and multimodal communication possibilities that exist within a significant disability context like Rett syndrome, deficit perspectives regarding communication challenges endure.…”
Section: Complex Communicationmentioning
confidence: 99%